2002
DOI: 10.1590/s0102-311x2002000200003
|View full text |Cite
|
Sign up to set email alerts
|

On the rumors about the silent spring: review of the scientific evidence linking occupational and environmental pesticide exposure to endocrine disruption health effects

Abstract: Occupational exposure to some pesticides, and particularly DBCP and chlordecone, may adversely affect male fertility. However, apart from the therapeutic use of diethylstilbestrol, the threat to human reproduction posed by "endocrine disrupting" environmental contaminants has not been supported by epidemiological evidence thus far. As it concerns other endocrine effects described in experimental animals, only thyroid inhibition following occupational exposure to amitrole and mancozeb has been confirmed in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 138 publications
0
41
0
9
Order By: Relevance
“…Many epidemiological studies have suggested the possible role of pesticides in the occurrence of cancers (Blair et al, 1992;Dich et al, 1997;Acquavella et al, 1998), neurological diseases (Colosio et al, 2003) or reproductive disorders (Cocco, 2002). Exposure assessment represents a critical concern in these studies Zahm, 1990, 1993;Garcia et al, 2000;Hamey, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiological studies have suggested the possible role of pesticides in the occurrence of cancers (Blair et al, 1992;Dich et al, 1997;Acquavella et al, 1998), neurological diseases (Colosio et al, 2003) or reproductive disorders (Cocco, 2002). Exposure assessment represents a critical concern in these studies Zahm, 1990, 1993;Garcia et al, 2000;Hamey, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…We are still far from reaching a consensus on DDT use for controlling endemic diseases. There is considerable evidence on DDT's adverse effects on the environment and human health 77 . Still, malaria is a serious public health problem in developing countries like those of Sub-Saharan Africa, leading to extensive mortality 81 .…”
Section: Resultsmentioning
confidence: 99%
“…According to some authors, the malaria cases and deaths that could be averted by DDT far outweigh the health problems arising from its use 81,82,83 . Meanwhile, others have shown a clear concern over the future use of DDT (even if rationally applied) for vector control 34,77 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant factors are familial inheritance, ultraviolet radiation, ionizing radiation, electromagnetic waves, chemical agents, viral infections, diet and interactions between children and environmental materials (Cocco, 2002;Cavdar, 1997;Buffer and Kyle, 1999). Early diagnosis has a significant importance in CC.…”
Section: Introductionmentioning
confidence: 99%